Karakteristik Akuifer Menggunakan Metode Geolistrik Resistivity Di Kecamatan Kota Tengah Kota Gorontalo - Rizky Hizrah Wumu; Ahmad Zainuri; Noviar Akase (Universitas Negeri Gorontalo, 2022)
Kota Tengah Subdistrict has the highest population density in Gorontalo City, with a population density of 6,755 people/km2. This high population density requires a large amount of water to meet the needs of the population, where one form of fulfillment is taken from groundwater. For this reason, it is necessary and important to know the characteristics of aquifers. This study aims to determine the characteristics of groundwater aquifers in the Kota Tengah Subdistrict. The method used is the resistivity geoelectric method to obtain aquifer characteristics in the form of material type (lithology), depth, and thickness of the aquifer. Based on the geoelectrical analysis in TS 01 there are 4 layers, namely topsoil, clay sand, sand, and clay; TS 02 contains topsoil, sand, and clay layers; TS 03 contains topsoil, sand, and clay. The study found that the lithology of the near-surface layer in the Kota Tengah subdistrict can be classified into aquifers and aquicludes. The aquifer layer is formed by sand-sized sedimentary deposits that have high permeability while the aquiclude is clay-sized which is impermeable. The aquifer layer was found starting from a depth of 0.57 m. The average thickness of the aquifer layer was 13.8 m which is interpreted as an unconfined aquifer. This study also found other deeper aquifer layers as confined aquifers that can not be further interpreted due to the limitations of the method used.